BUANG AIR BESAR SEMBARANGAN: FAKTOR BUDAYA TERHADAP KESADARAN MASYARAKAT UNTUK MENGATASINYA - Fitriani, Nera Shafira; Achdiani, Yani (Cahaya Ilmu Bangsa, 2025)
This article examines the practice of open defecation with a focus on the role of cultural factors in influencing public awareness to address it, particularly in Indonesia. Open defecation remains a global health issue affecting around 2 billion people, with negative impacts on health, the environment, and the economy. Culture, as a shaper of social norms, gender stigma, and mythological beliefs, often becomes a major barrier to changes in sanitation behavior. Through literature analysis and case studies, this article explains how traditional norms, such as the view of soil as a